Lockdown length and strength: labour-market effects in Germany during the COVID-19 pandemic - Anja Bauer; Enzo Weber (ZBW - Leibniz Information Centre for Economics, 2021)
This paper evaluates the short-term labour market impact of the COVID-19 containment measures in Germany. It examines two dimensions of the first lockdown in Germany, namely the length and the strength of the lockdown. While the assessment of the length is conducted via variation across regions and time in closing days and curfews, the latter uses the degree of closure in different sectors. For the length of the lockdown we find that an additional day of closure lead to an increase in the separation rate of 2.7 percent and a decrease in the jobfinding rate of 1.8 percent. For the strength of the lockdown the results show that a higher degree of closure increases separations and lower job findings to a similar extent. In both dimensions, we find that the effects are non-linear over time. Given this approach, we find that 31 percent of the considerably increased inflows from employment into unemployment, and 33 percent of the reduced outflows from unemployment to employment in the first wave were due to the treatment effect of the lockdown measures. In sum, the lockdown measures increased unemployment in the short run by 80,000 persons
Keywords: J6; E24; 330; containment measures; COVID-19; job finding rate; separation rate